Beneficial effects of a T. monococcum wheat cultivar on diabetes incidence evaluated in non-obese diabetic mice and after in vitro simulated gastroduodenal digestion. (3rd April 2022) - Rotondi Aufiero, Vera; Di Stasio, Luigia; Maurano, Francesco; Accardo, Francesca; Ferranti, Pasquale; Mamone, Gianfranco; Rossi, Mauro; Mazzarella, Giuseppe
Abstract: Wheat consumption can represent one of the nutritional factors involved in the onset of diabetes. We specifically investigated the potential diabetogenic effects of Hammurabi, a T. monococcum wheat cultivar, in non-obese diabetic (NOD) mice and analysed the levels of resistant starch in pasta manufactured with Hammurabi after in vitro gastroduodenal digestion. NOD mice were fed with Hammurabi, bread wheat or rice flour to evaluate diabetes incidence and insulitis score. An enzymatic method was applied to compare the content of resistant starch in Hammurabi pasta and durum wheat pasta (control). In NOD mice, the Hammurabi-based diet significantly delayed diabetes onset ( p = 0.0042) and reduced insulitis score compared to rice or wheat-based diet. Furthermore, the resistant starch value following in vitro digestion of Hammurabi pasta was significantly higher (4.08%) than that of durum wheat pasta (2.28%). Taken together, these results highlighted the potential positive effects of the Hammurabi-based diet on diabetes incidence.